2020
DOI: 10.3389/fcell.2020.00588
|View full text |Cite
|
Sign up to set email alerts
|

Tranilast Directly Targets NLRP3 to Protect Melanocytes From Keratinocyte-Derived IL-1β Under Oxidative Stress

Abstract: The activation of NLRP3 inflammasome-IL-1β pathway in keratinocytes contributes to the melanocyte death via autoimmunity-dependent manner in vitiligo. As a safe small-compound drug employed frequently in clinic, tranilast (TR) is newly reported to block the activation of NLRP3 inflammasome in macrophage. Nevertheless, whether keratinocyte-derived IL-1β damages melanocytes in an autoimmunity-independent way and whether TR could ameliorate the melanocyte damage via inhibiting the NLRP3-IL-1β pathway in keratinoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 34 publications
0
17
0
1
Order By: Relevance
“…Promising results of clinical trials for vitiligo using histamine solution also support the histamine induction of hypermelanosis in the surrounding skin in vitiligo [25]. Another possible new treatments are under investigation at present targeting epidermal keratinocytes [26][27][28][29][30].…”
Section: Discussionmentioning
confidence: 90%
“…Promising results of clinical trials for vitiligo using histamine solution also support the histamine induction of hypermelanosis in the surrounding skin in vitiligo [25]. Another possible new treatments are under investigation at present targeting epidermal keratinocytes [26][27][28][29][30].…”
Section: Discussionmentioning
confidence: 90%
“…Although, NLRP1 is regarded as the principal inflammasome sensor in human keratinocytes [ 87 , 96 , 108 ] expression of NLRP3 can also be detected in basal keratinocytes ( Figure 2 A) [ 128 , 129 ]. NLRP3 activation in human keratinocytes can be initiated by various signals [ 128 , 129 ] but without a need for a priming signal. Human keratinocytes respond to viral RNA with caspase-1 activation and subsequent IL-1β and IL-18 release, which is dependent on NLRP3 [ 129 ].…”
Section: The Nlrp Subfamilymentioning
confidence: 99%
“…Interestingly, intact skin of both human and mouse produce the same mediators upon the NLRP1 activating UVB exposure, but while in humans the process is mediated by NLRP1 in keratinocytes, in mouse skin the immune cells are responsible for this phenomenon [ 87 ]. Similarly, NLRP3 is also expressed and functional in human keratinocytes [ 128 , 129 ], but not in murine epidermis [ 171 ]. In human cells, NLRP10 regulates inflammasome activation [ 152 , 154 ], while Nlrp10 knock-out mice respond normally to inflammasome activation [ 155 , 156 ], suggesting a difference in function between the human and mouse proteins.…”
Section: Nlrs In Human and Mouse Skinmentioning
confidence: 99%
“…Oxidative stress (OS), defined as an imbalance between radical-generating and radical-scavenging activity, has been associated with a variety of diseases, including hypertension, diabetes, cancer and cardiovascular diseases (2,3). An increasing number of studies have indicated that the pathogenesis of vitiligo is associated with OS-mediated toxicity in melanocytes (4)(5)(6)(7). Previous studies have indicated that the state of OS commonly results in increased intracellular reactive oxygen species (ROS) production, which influences various signaling pathways leading to inhibition of melanin synthesis, destruction of cell structures and reduced survival of melanocytes (8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%